2007
DOI: 10.1111/j.1467-8276.2007.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Error in Recall Surveys and the Relationship between Household Size and Food Demand

Abstract: Variation in household survey design and implementation is used to obtain evidence of nonrandom measurement error in recall surveys of household expenditure. These surveys, which are used especially in developing countries, appear to have measurement errors in food expenditures and in food budget shares that are correlated with household size. These correlated errors may be part of the explanation for a puzzling pattern of falling food demand with rising household size in poorer countries. Copyright 2007, Oxfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 21 publications
2
58
0
Order By: Relevance
“…Existing empirical studies, however, demonstrate the opposite of the theoretical predictions, and thus the literature analyzing this "food puzzle" examines the theoretical implications of household scale economies and measures of household welfare (Logan forthcoming; Gibson and Kim 2007;Paxson 2003, 1998;Gan and Vernon 2003;Gibson 2002).…”
Section: Modelmentioning
confidence: 97%
“…Existing empirical studies, however, demonstrate the opposite of the theoretical predictions, and thus the literature analyzing this "food puzzle" examines the theoretical implications of household scale economies and measures of household welfare (Logan forthcoming; Gibson and Kim 2007;Paxson 2003, 1998;Gan and Vernon 2003;Gibson 2002).…”
Section: Modelmentioning
confidence: 97%
“…There is some consolation in this finding, as non-random, mean-reverting errors negatively correlated with true values bias regression coefficients even when just the dependent variable has error. When an explanatory variable has such error, its coefficient may be biased either toward or away from zero (Gibson and Kim, 2007). Moreover, the main correction for measurement error bias -instrumental variables (IV) -is inconsistent when errors are correlated with true values (Black et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that longer recall periods are associated with lower aggregate totals of frequent food expenditures. Gibson and Kim (2007) hypothesize that when respondents are asked to recall larger amounts of information from a greater number of transactions due to larger household size or longer recall period, they will shift from summing the total of individual remembered events to estimating the overall total. In a survey experiment in Papua New Guinea, Gibson (2002) found that the average food expenditure was 26% higher with a consumption diary (asking for consumption for each of the 7 days covered) than asking for one reported amount for the entire 7 days.…”
Section: Literature Reviewmentioning
confidence: 99%